Increased burden of suicidality among young street-involved sex workers who use drugs in Vancouver, Canada. (11th July 2018) - Barker, Brittany; Hadland, Scott E; Dong, Huiru; Shannon, Kate; Kerr, Thomas; DeBeck, Kora
Abstract: Background: The risks of suicidality among street-involved youth who use drugs and engage in sex work are not well described. This study sought to evaluate if street-involved youth who engage in sex work were at an elevated risk for attempting suicide. Methods: Data were derived from the At-Risk Youth Study, a prospective cohort of street-involved youth who use drugs in Vancouver, Canada. Multivariable generalized estimating equation analyses were employed to examine whether youth who engaged in sex work were at elevated risk of attempting suicide, controlling for possible confounders. Results: Between September 2005 and May 2015, 1210 youth were recruited into the cohort, of whom, 173 (14.3%) reported recently attempting suicide at some point during the study period. In multivariable analysis, youth who engaged in sex work were significantly more likely to report a recent suicide attempt (adjusted odds ratio = 1.93; 95% confidence interval: 1.28–2.91). Conclusions: Street-involved youth who engage in sex work were observed to be at a significantly higher risk for suicidality. Systematic discrimination and unaddressed trauma may contribute to the observed increased burden of suicidality among this population. Interventions that support the mental health and well-being of street-involved youth who engage in sex work are urgently needed.